Advances in Computing and Information Technology First International Conference, ACITY 2011, Chennai, India, July 15-17, 2011. Proceedings - Wyld, David C.; Wozniak, Michal; Chaki, Nabendu; Meghanathan, Natarajan; Nagamalai, Dhinaharan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the proceedings of the First International Conference on Advances in Computing and Information Technology, ACITY 2011, held in Chennai, India, in July 2011. The 55 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers feature significant contributions to all major fields of the Computer Science and Information Technology in theoretical and practical aspects.
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer software; Information storage and retrieval systems; Information systems; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Computer Communication Networks; Information Systems Applications (incl.Internet).; Software Engineering; Algorithm Analysis and Problem Complexity; Information Storage and Retrieval